Defining treatment success in rosacea as 'clear' may provide multiple patient benefits: results of a pooled analysis. (4th July 2017) - Webster, Guy; Schaller, Martin; Tan, Jerry; Jackson, J. Mark; Kerrouche, Nabil; Schäfer, Gregor
Abstract: Background: Rosacea treatment success is usually defined as a score of 1 ('almost clear') or 0 ('clear') on the 5-point Investigator Global Assessment (IGA) scale. Objective: To evaluate whether, after successful treatment, 'clear' subjects had better outcomes than 'almost clear' subjects. Methods: A pooled analysis was performed on 1366 rosacea subjects from four randomized controlled trials with IGA before and after treatment (ivermectin, metronidazole or vehicle). Assessments included the Dermatology Life Quality Index (DLQI) questionnaire and subject assessment of rosacea improvement. In one trial, patients were followed after the treatment period to measure time to relapse (IGA score ≥2). Results: At end of treatment, more 'clear' than 'almost clear' subjects had a clinically meaningful difference in DLQI (59% vs. 44%; p  < .001) and a final DLQI score of 0–1 indicating no effect on quality of life (84% vs. 66%; p  < .001). More 'clear' subjects reported an 'excellent' improvement in their rosacea (77% vs. 42%; p  < .001). The median time to relapse was more than 8 months for 'clear' vs. 3 months for 'almost clear' subjects ( p  < .0001). Conclusions: Achieving an endpoint of 'clear' (IGA 0) vs. 'almost clear' (IGA 1) is associated with multiple positive patient outcomes, including delayed time to relapse.